(untitled) (TAMADDUN NURI JURNALI, 2025)
This article analyzes the reforms implemented in Uzbekistan during the years of independence to increase the activity of women in the field of education and to support women, and the extent to which Uzbekistan’s indicators in world indices have increased in this regard.